Resveratrol ameliorates learning and memory impairments induced by bilateral hippocampal injection of streptozotocin in mice. (October 2022) - Wei, Ya-Dong; Chen, Xing-xing; Yang, Long-Jun; Gao, Xin-Ran; Xia, Qing-Rong; Qi, Cong-Cong; Ge, Jin-Fang
Abstract: Resveratrol (RES) is a polyphenol with diverse beneficial pharmacological activities, and our previous results have demonstrated its neuroprotective potential. The purpose of this study was to investigate the therapeutic effect of RES in Alzheimer's disease (AD)-like behavioral dysfunction induced by streptozotocin (STZ) and explore it's potential mechanism of action. STZ was microinjected bilaterally into the dorsal hippocampus of C5 7BL /6J mice at a dose of 3 mg/kg, and RES was administered intragastrically at a dose of 25 mg/kg for 5 weeks. Neurobehavioral performance was observed, and serum concentrations of insulin and Nesfatin-1 were measured. Moreover, the protein expression of amyloid beta 1–42 (Aβ1-42 ), Tau, phosphorylated Tau (p-Tau) (Ser396), synaptic ras GTPase activation protein (SynGAP), postsynaptic density protein 95 (PSD95), synapsin-1, synaptogomin-1, and key molecules of the Wnt/β-catenin signaling pathway in the hippocampus and prefrontal cortex (PFC) were assessed. Finally, pathological damage to hippocampal tissue was examined by Nissl and immunofluorescence staining. The results showed that compared with the controls, bilateral hippocampal microinjections of STZ induced task-specific learning and memory impairments, as indicated by the disadvantaged performances in the novel object recognition test (NOR) and Morris water maze (MWM), but not the contextual fear conditioning test (CFC). Treatment with RES could improve these behavioral disadvantages. The serum concentrations of insulin and Nesfatin-1 in the model group were remarkably higher than those of the control group. In addition, protein expression of Aβ1-42, Tau, and p-Tau (Ser396) was increased but expression of SynGAP, PSD95, brain-derived neurotrophic factor (BDNF), and p-GSK-3β/GSK-3β were decreased in the hippocampus. Although the protein expression of BDNF and SynGAP was also markedly decreased in the PFC of the model mice, there was no significant difference among groups in the protein expression of PSD95, BDNF, synapsin-1, synaptogomin-1, and p-GSK-3β/GSK-3β. RES (25 mg/kg) reversed the enhanced insulin level, the abnormal protein expression of Aβ1-42, Tau, and p-Tau (Ser396) in the hippocampus and PFC, and the hippocampal protein expression of SynGAP, PSD95 and BDNF. In addition, RES reversed the STZ-induced decrease in the number of Nissl bodies and the increase in fluorescence intensity of IBA1 in the hippocampal CA1 region. These findings indicate that RES could ameliorate STZ-induced AD-like neuropathological injuries, the mechanism of which could be partly related to its regulation of BDNF expression and synaptic plasticity-associated proteins in the hippocampus. Graphical abstract: Image 1 Highlights: The model mice bilaterally hippocampally microinjected with STZ presented task-specific learning and memory impairment. Bilateral hippocampal microinjections of streptozotocin induced β-amyloid deposition and synaptic plasticity imbalance in mice. RES could ameliorate STZ-induced AD-like neuropathological injuries, the mechanism of which might be partly involved in its regulation of the expression of BDNF and synaptic plasticity-associated proteins in the hippocampus.